ANALISIS PENGARUH VARIABEL EKONOMI MAKRO TERHADAP NILAI TUKAR RUPIAH - Rayhan, Danedo; Ananda, Candra Fajri (Journal of Development Economic and Social Studies, 2024)
Exchange rate is a key part of a country’s economic stability. The US Federal Reserve has been aggressively hiked the federal fund rates (Fed Rate), which potentially affect Indonesia’s rupiah exchange rate. Hence, it is interesting to understand the effect of Fed Rate hikes alongside other exchange rate determinants, i.e., BI Rate, inflation, trade balance, and foreign exchange reserves on the value of Rupiah exchange rate. This study uses Vector Autoregression (VAR) method to analyze data between 2018 to 2023. In line with what has often been assumed, this study found that Fed Rate hikes contribute to depreciation the value of Rupiah. On the other hand, policy reinforcement to maintain other macroeconomic indicators, such as inflation, trade balance position, and foreign exchange reserves will support the value of rupiah. Thus, it is essential for the government and the central bank of Indonesia to continuously monitor global economic policies and give adequate and immediate response to maintain Rupiah value.